A Byzantine Century - Palladino, Adrien (ED) (Masarykova univerzita, 2026)
This volume explores what it meant to invoke Byzantium during a century of restless political, cultural, and imperial transformation. From the 1820s to the 1920s, the “Neo-Byzantine” style was more than a matter of architectural taste in an age of eclecticism. It became a language of power and identity, called upon to serve colonial empires such as Britain, France, Russia, and Austria-Hungary, as well as contested regions like the Caucasus, the Balkans, and the Ottoman capital itself, where Byzantium was at once heritage and provocation. Far from being a marginal curiosity, the Neo-Byzantine revival was a crucible in which nations, religions, and empires negotiated their pasts and imagined their futures. Monumental churches, synagogues, and civic buildings across Europe, North Africa, and Western Asia were not simply constructed in a borrowed style: they materialized competing dreams of Byzantium, becoming instruments of political ambition, religious authority, national mythology, and cultural colonization.Through a series of case studies ranging from Dublin to Istanbul, from Marseille to Tbilisi, and from Prussian churches to diasporic Armenian projects, the contributors move between the macro and the micro, situating the style within broad historical currents while grounding it in the specificity of local histories. Together, they demonstrate how Byzantium was not only reinvented but actively contested — its image refracted through the shifting concerns of a global century.